Air Pollution Exposure Induces Vascular Injury and Hampers Endothelial Repair by Altering Progenitor and Stem Cells Functionality - Costa, Alice; Pasquinelli, Gianandrea (Frontiers in Cell and Developmental Biology, 2022)
Extensive evidence indicates an association of air pollution exposure with an increased risk of cardio-vascular diseases (CVDs) development. Fine particulate matter (PM) represents one of the main components of urban pollution but the mechanisms by which it exerts adverse effects on cardiovascular system remain partially unknown and under investigation. The alteration of endothelial functions and inflammation are among the earliest pathophysiological impacts of environmental exposure on cardio-vascular system and represent critical mediators of PM-induced injury. In this context, endothelial stem/progenitor cells (EPCs) play an important role in vascular homeostasis, endothelial reparative capacity and vasomotor functionality modulation. Several studies indicate the impairment of EPCs vascular reparative capacity due to PM exposure. Since a central source of EPCs is bone marrow (BM), their number and function could be related to the population and functional status of stem cells (SCs) of this district. In this review we provide an overview of the potential mechanisms by which PM-exposure hinders vascular repair by the alteration of progenitor and stem cells functionality.